MANIFESTATION OF COLLECTIVE SECURITY IN ASEAN AS A REGIONAL ORGANIZATION DURING PANDEMIC COVID-19 - Nur Afifah Ramadhani Musa; Agussalim Burhanuddin (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2024)
This research is entitled Manifestation of Collective Security in ASEAN as a Regional Organisation During the COVID-19 Pandemic. This research aims to identify ASEAN policies and efforts to realise collective security during the COVID-19 pandemic period. This research examines the manifestation of collective security in the Association of Southeast Asian Nations (ASEAN) as a regional organisation during the COVID-19 pandemic. The research method is to use a qualitative approach, combining desk research and data analysis. The results highlight ASEAN's important role in enhancing regional security through cooperation, particularly in the economic and diplomatic sectors, ASEAN utilises digital platforms for information exchange and coordination. The ASEAN Senior Officials Meeting on Health Development and the ASEAN Health Ministers Meeting facilitate open communication, allowing countries to share best practices and resources. For example, Thailand received early notification of COVID-19 through the ASEAN Emergency Operations Centre Network, enabling swift preparedness actions. The COVID-19 pandemic has demonstrated ASEAN's capacity to uphold its mission of regional stability and security. Through coordinated efforts, resource sharing, and international partnerships, ASEAN has effectively addressed the challenges posed by the pandemic. This experience underscores the importance of collective security and regional cooperation, reaffirming ASEAN's role as an important actor in maintaining stability and fostering resilience in Southeast Asia. This study concludes that ASEAN as a regional organisation plays an important role in ensuring the collective security of its members